PENGEMBANGAN KARIER APARATUR SIPIL NEGARA, PADA DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN BOLAANG MONGONDOW - Usup, Herdiawan (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract :In accordance with the Research Problem Formulation So The Purpose of This Research Is To Know How Career Development ASN / PNS done On Transportation Department, Communications and Informatics BolaangMongondowDistrict.Research Methods Used In This Research Is Qualitative Method.Moleong (2006) Said, qualitative research is research that intends to understand the phenomenon of what is experienced by research subjects (eg behavior, perception, actions, and others), holistically, and with The way descriptions are in the form of words and languages, in a particular context that is natural and by utilizing various natural methods (Moleong, 2009). Qualitative research aims to dig up and build a preposition or explain the meaning behind reality.According to the real results and the facts for his performance has been very good and trained from superiors to subordinates, and to about the potential for career development of the ASN in the communications service kominfo this is very good ,,, the level of ability and willingness it can be guaranteed pertained Good, but for the level of career development is relatively low, in because by some factors that may not be adequate .. while ASN has the right to have Development. The capacity of the apparatus is a right for ASN to gain useful expertise in supporting an organization as set forth in article 22 of Law Number. 5 Year 2014 on State Civil Apparatus. In the article it is mandated that every apparatus has the right to be developed by the government, both central government and local government.Based on the conclusions and the results of the study as described and discussed in it can be drawn conclusion as follows: ASN Competence (civil state apparatus) in career development and implementation of performance in view of the workings and the willingness to develop a career is very good but because Insufficient funds and the right to the right to development of ASN careers have not been obtained so ASN most of his career has not developed.Keywords: Development, Career.